Networked Air Defense Radar Resource Management Under Power and Tracking Constraints - O. Tuncer; Hakan Ali Cirpan (IEEE Access)
Air dominance plays a crucial role in today’s battlefield, and its importance has increased over time with the development of advanced platforms and commercial technologies that enable the proliferation of air threats. The importance of ground based air defense systems, which protect air space and critical infrastructure, is also increasing in line with the development of those air threats. It has come to a point where networking of those air defense systems is needed to further improve the overall effectiveness of air defense operations by sharing radar resources between them. Sharing resources is beneficial, especially in saturation constraints where a single radar’s tracking capacity is overwhelmed. Another important aspect is to lower the transmit power of the networked radars to decrease detectability from the adversary’s electronic warfare capability. This paper proposes a networked radar resource optimization methodology for fire control radars with limited tracking capacity and tries to minimize the transmit power of the networked radars while keeping the tracking quality needed for air defense engagement operations. Simulation results are presented for a sample scenario under saturation conditions. Numerical results show that with the proposed methodology, the targets are collaboratively tracked by the air defense radar network with the required tracking quality needed for engagement operations while minimizing the overall transmit power of the radar network.